2019
DOI: 10.1038/s41598-019-41923-6
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomised Double-Blind Study of the Tolerability and efficacy of repetitive Transcranial Magnetic Stimulation on Persistent Post-Concussion Syndrome

Abstract: This study investigates the effect of Repetitive Transcranial Magnetic Stimulation (rTMS) on persistent post-concussion syndrome (PCS). The study design was a randomized (coin toss), placebo controlled, and double-blind study. Thirty-seven participants with PCS were assessed for eligibility; 22 were randomised and 18 completed the study requirements. Half the participants with PCS were given an Active rTMS intervention and the other half given Sham rTMS over 3 weeks. Follow ups were at the end of treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 64 publications
2
60
0
Order By: Relevance
“…Though we did not see a correlation between improvement and time from mTBI in this small selection of patients, a study treating PCS using repetitive transcranial magnetic stimulation (rTMS), a different non-invasive brain stimulation device, found that patients that were within a year of their head trauma had a significant effect of treatment compared to those receiving sham treatment and those over 12 months post-trauma. 21 The data that support the findings of this study are available from the corresponding author upon request.…”
Section: Discussionsupporting
confidence: 60%
“…Though we did not see a correlation between improvement and time from mTBI in this small selection of patients, a study treating PCS using repetitive transcranial magnetic stimulation (rTMS), a different non-invasive brain stimulation device, found that patients that were within a year of their head trauma had a significant effect of treatment compared to those receiving sham treatment and those over 12 months post-trauma. 21 The data that support the findings of this study are available from the corresponding author upon request.…”
Section: Discussionsupporting
confidence: 60%
“…The exclusion criteria applied to each search included (i) non-peer or limited review conference proceedings, (ii) conference abstracts, (iii) books, (iv) theses (PhD, masters, honors), and (v) studies where single- or paired-pulse TMS was not the main technique. For example, data from related techniques such as transracial direct current stimulation (Wilke et al, 2017 ), repetitive TMS paradigms including theta-burst protocols measuring the intervention via TMS–EMG/TMS–EEG (Moussavi et al, 2019 ; Opie et al, 2019 ), or paired associative stimulation (De Beaumont et al, 2012a ) were used as interventions to explore other aspects of maladaptive plasticity, such that the influence of brain-derived neurotrophic factor in implicit learning (De Beaumont et al, 2012b ) was excluded as this was outside of the scope of this review.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed methodology for EVestG recordings is given in [1][2][3]9]. Briefly, EVestG recordings are made inside an electromagnetically shielded and sound attenuated (greater than 30dB) chamber.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that the EVestG responses are vestibuloacoustic and predominantly vestibular [1][2][3][4][5]. EVestG assessment has been applied to the detection of a number of pathologies including Alzheimer's Disease (AD) [5], Parkinson's Disease (PD) [6], Post-Concussion Syndrome (PCS [7][8][9], Vertiginous disorders [10][11][12], Major Depressive Disorder (MDD) [2], non-manic Bipolar Disorder [1] and the separation of Bipolar and MDD [13]. In previous studies we have collected Electrovestibulography recording data from Parkinson's Disease (PD), Alzheimer Disease (AD), Post-Concussion Syndrome (PCS), Major Depression and Bipolar Depression populations as well as a pool of healthy controls (N = 117).…”
Section: Introductionmentioning
confidence: 99%